Outsourcing de sistemas de información: Situación actual, evolución y tendencias - María Reyes González Ramírez; José Luis Gascó Gascó; Juan Llopis (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2015)
– The aim of this work is to describe in detail on the current situation of outsourcing of Information Systems using the results of a survey carried out in the biggest Spanish firms. This is a longitudinal study that covers 12 years, since the current results are contrasted with those of two surveys carried out previously in the same environment and by the same authors. The conclusions point to a preservation of the status quo in the configuration of the outsourcing and to a larger degree of maturity in the characteristics of the contracts.
Keywords: M10; M15; M55; 330; Information systems; Information technologies; Outsourcing; Survey; Providers